Adaptive Mechanism Based on Shared Learning in Multi-agent System - Li, Qingshan; Chu, Hua; Diao, Liang; Wang, Lu (Intelligent Information Processing VII, 2014)
In view of the deployment environment of the adaptive system is complex, dynamic, unpredictable, focusing on the construction of dynamic, uncertain environment adaptive system, and this paper combines the reinforcement learning technology and software agent technology to propose an adaptive mechanism based on shared learning in multiple agent system. Based on this, framework for constructing adaptive systems and shared learning algorithm of agent are given. Finally, by conducting a comparative experiment and result analysis to verify the feasibility of the theory put forward by this article.